Some observations on the morphology of Sclerasterias richardi a rarely encountered Mediterranean Sea star (Echinodermata: Asteriidae) - MASTROTOTARO, F.; MIFSUD, C. (Mediterranean Marine Science, 2008)
The presence of specimens of the asteroid Sclerasterias richardi(Perrier, 1882) in Maltese waters, with some new details of its morphology (observed by SEM) and with special reference to its madreporites, is reported.